Violin Concertos [de Wolfgang Amadeus Mozart] = Violinkonzerte [de Wolfgang Amadeus Mozart] = Concertos pour violon [de Wolfgang Amadeus Mozart] = Concerti per violino [de Wolfgang Amadeus Mozart] - Mozart, Wolfgang Amadeus ((Complete Mozart Edition ;)
Contiene: 1) Violin Concerto in B Flat, KV 207; 2) Violin Concerto in D, KV 211; 3) Violin Concerto in G, KV 216; 4) Adagio for Violin and Orchestra in E, KV 261; 5) Violin Concerto in D, KV 218; 6) Violin Concerto in A, KV 219; 7) Rondo for Violin and Orchestra in B Flat, KV 269/261a; 8) Rondo for Violin and Orchestra in C, KV 373; 9) Violin Concerto in D, KV 271a/271i; 10) Concertone for 2 Violins and Orchestra in C, KV 190/186E; 11) Sinfonia Concertante in E Flat, KV 364/320d; 12) Concerto for Violin, Piano and Orchestra in D, KV App. 56/315f; 13) Sinfonia Concertante in A, KV App. 104/320e.